Distributive and self-sustainable scheduling algorithm for wireless sensor networks - Sheikh, M.A. (2013)
Scheduling or allocation of resources becomes one of the fundamental problems in wireless networks when several nodes contend to access a single and a common medium. To design a scalable wireless network, the slot scheduling algorithm must be computationally simple and distributive. In the past, many scheduling algorithms were proposed. However, when these techniques were implemented in dense networks, they often lacked the scalability factor due to node failure and dynamic topology changes. Thus, the design of optimal distributed scheduling algorithm has remained a challenge for the last few decades. In this paper, we propose a distributive and self-sustainable scheduling algorithm (DSSA). DSSA is a schedule based protocol and the objective of the algorithm is to assign the time slots to the nodes and avoid collision. DSSA is a simple, distributed and performance optimal scheduling algorithm and overcomes a variety of slot scheduling problems. DSSA resolves slot scheduling challenges by presenting a novel heuristic approach. The proposed technique is not centralized, hence it is distributive. It is fair and simple in terms of implementation, because the node which REQUEST first is given a priority to schedule its slot. Moreover, it is robust against any dynamic change without incurring extra message overhead and, utilizes minimal resources to provide an optimal collision free transmission. Simulation results show that DSSA is more performance optimal than the distributed randomized scheduling algorithm DRAND in terms of energy consumption, message overhead and execution time. Â© 2013 IEEE.